Sebaran Sarang Penyu Hijau (Chelonia mydas) Di Kawasan Konservasi Pesisir Dan Pulau-Pulau Kecil (Kkp3k) Paloh Desa Sebubus Kabupaten Sambas - Romiyansah, Romiyansah; Nurdiansyah, Syarif Irwan; Apriansyah, Apriansyah; Risko, Risko (Oseanologia, 2024)
This research aims to determine the distribution pattern of green turtle nests (Chelonia mydas) in the KKP3K Paloh area, Sebubus Village, Sambas Regency. This research was carried out in October 2021 in the Paloh Conservation, Coastal and Small Islands Conservation Area (KKP3K), Sebubus Village, Sambas Regency. The method used in this research is the purposive sampling method (Indriyanto, 2006). The sampling location was determined based on the landing location of the turtles to lay their eggs, then the results of the field survey were obtained in two segments, namely segment 2A and segment 3A which consisted of 15 sectors. Based on the results of 14 days of research, the total number of green turtles that came ashore and made nests in two segments was 234 green turtles. The number of green turtles that came ashore and made nests in segment 2A was 153 green turtles, the number of green turtles with egg-laying status was 108 nests and the number of green turtles with non-laying status was 45 nests. Meanwhile, the number of green turtles that came ashore and made nests in segment 3A was 81 green turtles and the total number of green turtles found in nesting status was 50 nests and the total number of green turtles found in non-nesting status was 31 nests. Sector 8 is a place where many turtles lay their eggs with an average nest temperature of 290C in 27 nests. The morisita index (distribution) of egg-laying and non-laying green turtles (Chelonia mydas) in segment 2A totaled 156 nests and in segment 3A totaled 78 nests, the morisita index Id was 1, so the population distribution was in the uniform category. Based on direct observations in the field, there are several factors that influence green turtles to lay eggs and not lay eggs. Factors influencing green turtles in the process of making egg nests are the temperature conditions of the nest that allow it and the conditions of the surrounding environment such as rubbish and the slope of the beach which is not in the form of a cliff or steep.